(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article comprehensively analyzes the issues of improving the financing system of higher education institutions in the Republic of Uzbekistan. The large-scale reforms being carried out in the field of education in the country require increasing the efficiency of financial mechanisms in training personnel in line with the requirements of the modern economy. The article first of all analyzes the current financing system in Uzbekistan and assesses its historical evolution, legal and regulatory framework and current state. The advantages and disadvantages of financing through funds allocated from the state budget, targeted programs, grant and contract-based forms of education are indicated. The experience of foreign countries, including Finland, Germany, South Korea and the USA, is also analyzed. Diversified models of financing in these countries and forms of public-private partnership are considered as promising solutions for Uzbekistan.